THE ROLE OF PHRASEOLOGICAL UNITS IN CROSS-CULTURAL COMMUNICATION - Marjona Akmal qizi Ramazonova (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract. This article examines the role of phraseological units in cross-cultural communication and language learning. Phraseological units, including idioms, proverbs, collocations, and fixed expressions, are important elements of every language because they reflect cultural traditions, national mentality, and historical experience. The study analyzes the structural and semantic features of phraseological units and discusses their communicative and stylistic functions. Special attention is given to the difficulties of understanding and translating phraseological units between languages.